Prevalence of diabetes mellitus in a rural population of north India - Kumar, Ashok; Bano, Tanveer; Garg, Sunil Kumar; Singh, Ganesh; Kumar, Sanjeev (International Journal Of Community Medicine And Public Health, 2020)
Background: Diabetes is the serious public health problem in all the countries but majorly in developing countries. The prevalence of diabetes is showing an upward trend in most countries. The prevalence of diabetes is rapidly rising in rural population. Also, there is paucity of data regarding diabetes mellitus in rural Meerut. The aim of the study was to study the prevalence of diabetes mellitus and Associated factors with diabetes mellitus. A cross- sectional study. Methods: By taking the prevalence of diabetes mellitus 13% in persons age 30 years and above by various studies and relative precision 20% the sample size come out to be 642, total subjects studied were 700 for uniform coverage in villages selected by systematic random sampling, fasting blood sugar was done to estimate the prevalence of diabetes. Rest of the information was collected on predesigned and pretested questionnaire. Results: The prevalence of diabetes were found to be 11.7% in persons aged 30 years and above in rural population of Meerut. The prevalence of diabetes was found to be significantly associated with increasing age, family history, social status and body mass index. Conclusions: The diabetes mellitus is a significant health problem after 40 years of age in rural population.